Soil salinity and nutrients pattern along a distance gradient in coastal region - S. Ahmed; I. Kayes; S.A. Shahriar; M. Kabir; M.A. Salam; S. Mukul (Global Journal of Environmental Science and Management)
Soil salinity is considered as one of the major challenges in coastal agriculture in Bangladesh yet geographical extent of soil salinity and nutrients status have received little or no attention. This study investigated the patterns of soil salinity, total nitrogen, phosphorous, potassium and sulfur between agricultural and fallow land along a 90 km distance from the coastline in Noakhali, Bangladesh. Soil samples were collected from three depths (0, 10, and 30cm) in four different locations from coastline towards inland (0, 30, 60, and 90km) following a systematic random sampling. Soil salinity and total nitrogen, phosphorous, potassium and sulfur were analyzed by fitting fixed effect linear models for a full factorial design and then inverse distance weighted interpolation technique was applied to map spatial patterns of selected soil parameters. Highest soil salinity and sulfur were recorded in surface soils at coastline (0 km), whereas least in 90 km far from coastline. Soil depth resulted significant differences in phosphorous, potassium and showed significant interactions among the distant points. This study delineates the soil nutrients patterns and salinity as baseline information to explain salinity driven soil nutrient dynamics in coastal region of Bangladesh.